Follow-up on Recommendations on The Investigation Results (TLRHP) of The BPK RI on Regional Government Financial Reports in Kotamobagu City - Tampangela, Cintiarita W.A; Masengi, Evi Elvira; Mokat, Jetty E. H (JUPE : Jurnal Pendidikan Mandala, 2023)
BPK audits are carried out on the Central Government, Regional Government, other State Institutions, Bank Indonesia, State-Owned Enterprises, Public Service Agencies, Regional-Owned Enterprises and other Institutions or Bodies that manage state finances. The audits in question include financial audits, performance audits, and audits with specific objectives. BPK audit results express opinions on financial reports, conclusions and recommendations for implementation performance, services, activities, government programs, as well as conclusions on the implementation of the internal control system and compliance with statutory provisions. Regional Government Finance in Kotamobagu City. This research uses a qualitative paradigm approach through direct interviews and documentation studies. Researchers have an important role in selecting relevant informants as data sources, collecting data, and processing the data obtained. Next, the researcher will carry out data analysis, validate the data, and draw conclusions from the research results according to the actual situation. The results of the research found that follow-up to audit results has a strategic role in the supervision cycle of government administration, because the success or failure of supervision can be seen or measured from the progress of the follow-up, so that understanding the method/mechanism for implementing the resolution of the Follow-up to Recommendations on BPK Audit Results needs to be a concern for implementation. In accordance with the commitment, there needs to be a special team to handle follow-up, not focusing on just one person, so as to facilitate the process of coordinating and completing follow-up recommendations.